2015
DOI: 10.1093/ndt/gfv421
|View full text |Cite
|
Sign up to set email alerts
|

Induction of cardiac FGF23/FGFR4 expression is associated with left ventricular hypertrophy in patients with chronic kidney disease

Abstract: Our results indicate a strong association between LVH and enhanced expression levels of FGF23, FGFR4 and calcineurin, activation of NFAT and reduced levels of soluble Klotho in the myocardium of patients with CKD. These alterations are not observed in kidney transplant patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

16
145
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 181 publications
(171 citation statements)
references
References 59 publications
16
145
1
1
Order By: Relevance
“…In autopsy studies of children with advanced CKD, the upregulation of FGF23 and FGFR4 expression in heart tissue were associated with fibrosis [24], a known precursor of diastolic dysfunction, HF, and arrhythmia. In addition, FGF23 can induce a spike in intracellular calcium in cardiomyoctes and alter contractility, physiology predisposing to SCD [27,28]. Thus, the findings in the present study support the biologic effects of FGF23.…”
Section: Discussion/conclusionsupporting
confidence: 80%
See 1 more Smart Citation
“…In autopsy studies of children with advanced CKD, the upregulation of FGF23 and FGFR4 expression in heart tissue were associated with fibrosis [24], a known precursor of diastolic dysfunction, HF, and arrhythmia. In addition, FGF23 can induce a spike in intracellular calcium in cardiomyoctes and alter contractility, physiology predisposing to SCD [27,28]. Thus, the findings in the present study support the biologic effects of FGF23.…”
Section: Discussion/conclusionsupporting
confidence: 80%
“…In rodent models, FGF23 induces cardiac hypertrophy mediated by FGFR4 [2,25,26]. Genetic ablation of FGFR4 can prevent the induction of LVH by FGF23 in rodent models of CKD and aging [27]. In autopsy studies of children with advanced CKD, the upregulation of FGF23 and FGFR4 expression in heart tissue were associated with fibrosis [24], a known precursor of diastolic dysfunction, HF, and arrhythmia.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…FGF23 can play a physiological role through classical Klotho -dependent and non-dependent pathways, which require receptor FGFR1c or FGFR4 involvement [6]. Klotho provides a binding site for the C-terminus of FGF23 and then binds to the receptor FGFR through the N-terminus of FGF23 to activate the classical Klotho-dependent pathway [7]. However, with the progress of CKD, FGF23-Klotho axislose balance.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, although no differences were observed in FGFR1 expression in myocardial tissue from cases and controls, FGFR4 mRNA expression was higher in cases than controls and higher in LVH(+) cases compared with those without LVH where it was correlated positively with cardiomyocyte cross-sectional area and FGF23 expression. Finally, mRNA FGF-23 as well as myocardial expression of the regulatory subunit of calcineurin and NFAT were higher in cases with LVH as compared with those without LVH (30). Of note, previous studies in experimental CKD have shown that complete inhibition of FGF-23 activity prevents the development of LVH and secondary hyperparathyroidism but it is associated with increased mortality linked to hyperphosphatemia and vascular calcifications [31].…”
mentioning
confidence: 89%